Treatment of Diabetes and Hyperlipidemia with Extracts of Eugenia Jambolana Seed and Aegle Marmelos Leaf Extracts in Alloxan Induced Diabetic Rats - SHIVANAND PANDEY (International Journal of Pharma and Bio Sciences, 2010)
The present study was carried out in rats to test the efficacy of aqueous combined extract of E.jambolana and A .marmelos on serum insulin, hyperglycemia and serum lipid profile changes associated with diabetes. Eugenia jambolana and Aegle marmelos are used extensively in the indigenous system of medicine as an anti-diabetic agent. The current investigation focuses on the serum insulin augmentation, anti-hyperglycemic and anti-hyperlipidemic property of a combined aqueous extracts of E.jambolana and A.marmelos (EA) on alloxan induced diabetic rats. The diabetes induced animals were fed with plant extracts at the increasing dosage of 200mg, 300mg and 400mg of body wt. The combined plant extracts administrated animals revealed a significant (P<0.001) increment of serum insulin levels, higher reduction in hyperglycemia and hyperlipidemia when compared to the diabetic control rats (P<0.001).